1985
DOI: 10.1080/02724936.1985.11748355
|View full text |Cite
|
Sign up to set email alerts
|

BCG test reaction in previously BCG vaccinated children

Abstract: BCG test reactions were studied in 1095 non-tuberculous children from 6 months to 5 years of age, who had received BCG vaccination in the newborn period, in order to find out the diagnostic value of the BCG test in previously BCG vaccinated children. Previous BCG vaccination has an effect on the BCG test reaction in the form of an accelerated BCG reaction. Although the degree of reaction decreases with time, 51.4% of children still showed a strongly accelerated BCG reaction 4 1/2-5 years after BCG vaccination.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
8

Year Published

1987
1987
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 1 publication
0
5
0
8
Order By: Relevance
“…Myint et al 16 realizaram a triagem prévia de sua casuística com o uso do PPD Rt-23. Poder-se-ia, então, perguntar se a realização desta mesma triagem não deveria ter sido feita em nossa casuística.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Myint et al 16 realizaram a triagem prévia de sua casuística com o uso do PPD Rt-23. Poder-se-ia, então, perguntar se a realização desta mesma triagem não deveria ter sido feita em nossa casuística.…”
Section: Discussionunclassified
“…A mais completa referência mundial a respeito do BCGteste em sadios previamente vacinados com BCG-id é o trabalho de Myint et al 16 Neste, foram aplicados o PPD Rt-23 1,0 TU e a BCG congelada ressecada japonesa, e considerados os grupos por sexo e adequação nutricional. Os dados de 1095 crianças consideradas não tuberculosas foram analisados, apresentando 57,4% de reações superiores a dez milímetros e, se considerados apenas os eutróficos, uma porcentagem ainda maior, atingindo a cifra de 62,6%.…”
Section: Intervalo Entre a Primovacinação Com Bcg-id E O Bcg-teste (Eunclassified
See 2 more Smart Citations
“…Mantoux test may be affected negatively by such factors as severe malnutrition, steroid, and cytotoxic therapy. 3,4 Immunosupression induced by ultraviolet rays (UVR) has been shown to alter the skin response to the Mantoux test negatively. [5][6][7][8][9] Furthermore, It has been observed that even modest doses of UV rays can significantly reduce local delayed type IV hypersensitivity (DTH) response to recall antigens, and that recent sun exposure should be considered a possible cause of false negative Mantoux response.…”
Section: Introductionmentioning
confidence: 99%